The impact of patient capital on job quality, investments and firm performance - Sommer, Christoph (Deutsches Institut für Entwicklungspolitik gGmbH, 2021)
Despite its importance for development, long-term finance is particularly scarce in countries with lower income levels. This not only results in unrealised growth and employment creation at the national level and at the level of individual firms, but also undermines a broader shift towards better jobs. After all, many long-term investments comprise investments in labour that have the potential to contribute to improvements in the quality of jobs, through training to boost skill levels, the creation of more stable employment relationships, and the higher wages that result. This paper uses more than 17,000 firm-level observations from 73 mostly low-and middle-income countries between 2002 and 2009 to provide the first empirical evidence of the extent to which long-term finance affects the quality of jobs. Additionally, it looks into effects on investments and the performance of firms. The findings, based on inverse probability weighted regression adjustment, indicate that firms with long-term finance exhibit a share of permanent employees that is 0.9 percentage points higher, and train an additional 2.4 per cent of their production workers. The probability that firms invest in fixed assets or in innovations in their production process both increase by more than 5.5 percentage points, while employment and sales growth rises as well. The fact that the positive effects on job quality mostly disappear when defining long-term finance as loans with a maturity of more than one year instead of more than two years, underlines the importance of longer loan maturities for better jobs. Despite presenting favourable theoretical and descriptive arguments, it cannot be ruled out completely that unobservable variables affect the estimation of effect sizes.
10.23661/dp6.2021
Keywords: Graue Literatur; Fremdkapital; Kredit; Dauer; Bildungsinvestition; Qualifikation; Investition; Unternehmenserfolg; Schätzung; Entwicklungsländer; Schwellenländer; Soziale Situation; Arbeitsmarkt; Finanzierung; Klein- und Mittelbetrieb